Software Project Management Using Machine Learning Technique - A Review - Hazil M.Z.M.; Mahdi M.N.; Mohd Azmi M.S.; Cheng L.K.; Yusof A.; Ahmad A.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Machine learning; Risk assessment; Risk perception; Software design; Development performance; Machine learning techniques; Management analysis; Management planning; Project performance; Project risk assessment; Software project; Software project management; Project management